Primary sclerosing cholangitis in a cohort of South African petients with inflammatory bowel disease at Charlotte Maxeke Johannesburg Academic Hospital - Alshmandi, Mohamed Almokhtar Mohamed (My University, 2018)
Background: Primary Sclerosing Cholangitis (PSC) is a chronic, progressive cholestatic liver disease of unknown aetiology. PSC has a very strong association with Inflammatory Bowel Disease (IBD). The phenotype in patients with PSC alone can be different to that of patients with both PSC and IBD (PSC-IBD). The incidence and prevalence of PSC varies considerably in Asian and Western studies.1 The differences in the epidemiological data recorded suggest that the presentation of PSC may vary in different populations. There is a dearth of information on this topic from African countries in general and more specifically in the Black South African population. Aim: The aims of this study are to: 1- Describe the demography, clinical features, laboratory findings, radiographic imaging and outcome of subjects with PSC with a particular emphasis on the Black South African cohort. 2- Compare the findings in patients with isolated PSC to those with PSC-IBD. Methods: This study was a retrospective chart review of 305 patients with PSC and/or IBD. The study focused on patients with PSC and PSC-IBD. The patients were seen at the Gastroenterology clinic at Charlotte Maxeke Johannesburg Academic Hospital (CMJAH), a tertiary academic hospital affiliated to the University of the Witwatersrand in Johannesburg, South Africa. The study period extended from 1 January 2008 to 31 May 2014. The data was extracted using a structured data sheet (see Appendix A). The data was captured in Microsoft Excel and later exported into Statistical Product and Service Solutions (SPSS). Descriptive statistics were used to summarize the demographic data of the study cohort in general and separately for the Black African sub-group. The Chi-square test of association was used to assess whether there were any association between PSC and the following factors: gender; ethnicity and a history of smoking. Results: There were 69 patients with PSC. There was an almost equal distribution between females (51%) and males (49%). In females the age at diagnosis was marginally higher (42 years) than in males (39years). The majority of the cohort was Black African (68%); the rest comprised Whites (15%); Asians (13%) and Coloureds (4%). The demography; clinical and radiological findings and outcomes in the Black African group were similar to the rest of the cohort. The one significant difference noted between the two groups was the frequency of liver cirrhosis which was more common in the other race groups. There was an almost equivalent distribution between patients with PSC alone (49%) and those with PSC-IBD (51%). At initial presentation the majority of patients (60%) had features indicative of PSC; almost one quarter (26%) had IBD and the remainder of the patients had features of PSC-IBD. The demography; clinical and radiological findings was similar in patients with PSC when compared to those with PSC-IBD. The significant differences noted between the two groups were the higher detection rate of isolated common bile duct involvement in patients with PSC and the increased colonic involvement in patients with PSC and Ulcerative Colitis (UC). Conclusions In our setting patients with PSC, including specifically the Black African cohort have a similar profile in terms of demography, clinical, laboratory and imaging findings to previously described large cohorts in the western world.1 This study didn’t reveal any association between the PSC or PSC-IBD and ethnicity or gender. The study showed that smoking conferred a protective effect against the development of PSC. The data in this study supports the observations of other studies that colonic inflammation is important for PSC development particularly with ulcerative colitis. An underlying history of IBD and autoimmune disorders should be sought in patients with PSC.
A research report submitted to the Faculty of Health Sciences, University of Witwatersrand, in fulfilment of the requirements for the degree of Master of Medicine in the branch of Internal Medicine. Johannesburg, 2018.
Keywords: Cholangitis, Sclerosing; Inflammatory Bowel Diseases; Liver Diseases